2017
DOI: 10.1590/s1677-5538.ibju.2016.0064
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hormonal activity in patients with premature ejaculation

Abstract: PurposePremature ejaculation is considered the most common type of male sexual dysfunction. Hormonal controls of ejaculation have not been exactly elucidated. The aim of our study is to investigate the role of hormonal factors in patients with premature ejaculation.Materials and MethodsSixty-three participants who consulted our outpatient clinics with complaints of premature ejaculation and 39 healthy men as a control group selected from volunteers were included in the study. A total of 102 sexual active men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Carani et al 15 48 (34 hyperthyroid Rate of hypothyroidism was 1.1% in the general population and 2.5% in the sexual clinic population. Rate of hyperthyroidism was similar in the two populations (3.5 vs 3.4%).…”
Section: Study N Findingsmentioning
confidence: 94%
See 2 more Smart Citations
“…Carani et al 15 48 (34 hyperthyroid Rate of hypothyroidism was 1.1% in the general population and 2.5% in the sexual clinic population. Rate of hyperthyroidism was similar in the two populations (3.5 vs 3.4%).…”
Section: Study N Findingsmentioning
confidence: 94%
“…37 In another case-control study of 63 men with PE and 39 controls by Canat et al, no differences in free T3 or free T4 (p>0.05) were observed, but TSH levels were significantly lower in men with PE (p=0.017). 38 Waldinger et al performed an observational study of 620 men with lifelong PE, which was defined as IELT less than 1 minute since first sexual intercourse experience with all partners >90% of the time. The authors observed that rates of hypo-and hyperthyroidism in men with lifelong PE were not significantly different than those in the general population (p>0.05).…”
Section: Premature Ejaculation and Hyperthyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…PE has always been a worrying condition whose research of the mechanism has raised several theories: psychogenic, neurobiological, genetic and hormonal [6]. Among our respondents (303), 42.2% identified themselves as PE while 57.4% did not.…”
Section: Discussionmentioning
confidence: 85%
“…[ 2 ] Recently, the prevalence of PE has been 26.67% according to the study of Benha University. [ 3 ] Several studies suggest that the etiology of PE includes a range of biological and psychological factors such as luteinizing hormone, prolactin, thyroid-stimulating hormone, diabetes, testosterone, [ 4 , 5 ] erectile dysfunction, infertility, lower urinary tract symptoms, and varicocele (VC) also have been recognized as risk factors for PE. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%